On the Empirical Estimation of Utility Distribution Damping Parameters Using Power Quality Waveform Data. (15th March 2007) - Hur Hur, Kyeon Kyeon; Santoso Santoso, Surya Surya; Gu Gu, Irene Y. H. Irene Y. H.
Abstract : This paper describes an efficient yet accurate methodology for estimating system damping. The proposed technique is based on linear dynamic system theory and the Hilbert damping analysis. The proposed technique requires capacitor switching waveforms only. The detected envelope of the intrinsic transient portion of the voltage waveform after capacitor bank energizing and its decay rate along with the damped resonant frequency are used to quantify effective X/R ratio of a system. Thus, the proposed method provides complete knowledge of system impedance characteristics. The estimated system damping can also be used to evaluate the system vulnerability to various PQ disturbances, particularly resonance phenomena, so that a utility may take preventive measures and improve PQ of the system.